Non-invasive monitoring of multiphase flows - Chaouki, J.; Larachi, Faical; Dudukovic, Milorad P., 1944- (Elsevier, 1997)
Non-Invasive Monitoring of Multiphase Flows is a result of the latest advances realized in non-invasive measurement of multiphase systems by means of various tomographic and velocimetric techniques. Written by experts on special topics within the realm of this subject, the book reviews in 15 chapters the theoretical background and the physics of the measurement process for each of a number of techniques. In addition, the mathematical modeling related to the measured property, such as in the image reconstitution problem for tomography, successful application of the techniques for measurement in various multiphase systems and their advantages and limitations are described. Features of this book: - Comprehensive and Complete. Covers both theoretical and application viewpoints of noninvasive measuring techniques in multiphase systems. There is no book available on this subject in the field of multiphase flows - Versatile. Material is presented in such a way that the book can be used either for research or for teaching graduate students specializing in the topic of multiphase flows - Awareness and Uniformity. The engineering community is made aware of advantages of these new techniques and they are presented in a uniform package. The editors strive to provide a comprehensive compendium of all the relevant information essential for practising engineers, consultants, university professors, graduate students and technicians who are involved in the study of multiphase flow phenomena. The book, although directed to the study of multiphase systems of interest to the chemical engineer, also provides valuable information for all other engineering disciplines that deal with multiphase systems.